Analisis Kebugaran Jasmani Peserta Didik Sekolah Dasar di Daerah Pinggir Pantai, Dataran Tinggi, dan Pegunungan Kota Padang - Roby Jasmanedi; Eri Barlian; Yendrizal; Gusril; Firman; Randi Kurniawan (Jurnal Penelitian Pendidikan IPA, 2025)
Physical fitness is a determining factor for human growth and development. From the age of 6 years to 18 years the process of growth and development is very rapid. The purpose of this study was to see how the growth and development of students aged 10-12 years or phase c using the TKSI test with 5 items tested. This type of research uses comparative descriptive research which involves collecting data from two or more different groups to understand the differences between them. The subjects of this study were 3 elementary schools based on geographical location. The research instrument used was the Indonesian student fitness test (TKSI) with test items Shuttle Shuttle Run 4x10 m Get ball, 600m Run, Child Ball, Tok Tok Ball and 30 seconds Baring Sitting. The test used One Way ANOVA and test norms that already exist in the Indonesian student fitness test book (TKSI). Data were processed using IBM SPSS 24 and Microsoft excel. This study shows the average physical fitness of students at SDN 19 Air Tawar Barat (16.31), SDN 08 Surau Gadang (17.55), and SDN 13 Batu Gadang (18.25). There was a significant difference in the level of physical fitness between the three schools. In conclusion, the physical fitness level of students at SDN 13 Batu Gadang is better than that of SDN 08 Surau Gadang and SDN 19 Air Tawar Barat, with a difference of 1.94 and 0.7 respectively.